DNA and the chromosome – varied targets for chemotherapy - Nelson, Stephanie M (BioMed Central, 2004)
The nucleus of the cell serves to maintain, regulate, and replicate the critical genetic information encoded by the genome. Genomic DNA is highly associated with proteins that enable simple nuclear structures such as nucleosomes to form higher-order organisation such as chromatin fibres. The temporal association of regulatory proteins with DNA creates a dynamic environment capable of quickly responding to cellular requirements and distress. The response is often mediated through alterations in the chromatin structure, resulting in changed accessibility of specific DNA sequences that are then recognized by specific proteins. Anti-cancer drugs that target cellular DNA have been used clinically for over four decades, but it is only recently that nuclease specific drugs have been developed to not only target the DNA but also other components of the nuclear structure and its regulation. In this review, we discuss some of the new drugs aimed at primary DNA sequences, DNA secondary structures, and associated proteins, keeping in mind that these agents are not only important from a clinical perspective but also as tools for understanding the nuclear environment in normal and cancer cells.